Gli atteggiamenti degli insegnanti di scuola elementare nelle scienze biologico-naturalistiche - Tonucci, F.; Consoli, V.; Di giovanni, I.; Messina, A.; Rusca, G.; Nardis, E. de; Primucci, P. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This paper stresses the need of coherence between the science teachers training and the emergent constructivist model of science learning.